The Role Of Pancasila In Growing The Soul Of Nationalism For The Millenial Generation - Masruroh Masruroh (Mimbar Agama Budaya, 2022)
The entry of the era of globalization makes the world's nations almost have no boundaries. The good and bad impact of globalization, of course, let's examine it together by basing Pancasila as a way of life for the Indonesian people in facing all problems along with the times. The research methodology that we use in this study is quantitative. The number of samples taken were 32 students of chemistry education at UIN Syarif Hidayatullah Jakarta. The data collection technique that researchers used in this observation was a questionnaire. The results of the questionnaire distributed to students resulted in several steps that could be taken from the role of Pancasila in fostering the spirit of nationalism of the millennial generation, including by applying the role of Pancasila values which can foster the spirit of nationalism in general, namely by applying the values of Pancasila in everyday life, respecting differences, use the good and correct Indonesian language, participate responsibly in maintaining independence according to ability, love domestic products, put the interests of the state above personal interests, preserve the nation's culture, love the diversity of Indonesia.